LANGUAGE POWER: VIOLATING THE MAXIM OF QUALITY TO ACHIEVE GOOD COMMUNICATION AND TO KEEP CREDIBILITY - Yusuf, Adi (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
One of various aspects to a series of activities on successful business is really influenced by theappropriate use of language. Public Relations (PR) people, in order to make good communication withtheir business partners, indeed need to have good understanding on language uses so that the businessactivities are successful. One of the language uses can be identified through the principle ofcommunication, called “maxims”. The purpose of this paper is to describe the use of language andcontexts which lead us to violate the maxim of quality. This research used a descriptive qualitativemethod. It was found that language may be used as a means to achieve enormous influence in a series ofmarketing campaign. In addition, in line with the use of ‘the maxim of quality’, low power publicrelations in a certain situation need to violate it in order to achieve good communication and to makebusiness activities successful at last. Furthermore, “a white lie” or “no comment” may become analternative way to make the hearer pleased and to save one’s credibility.